New World remakes, Cold-War politics, and the legacy of the Bauhaus - Wünsche, Isabel (Peripeti, 2023)
This essay explores the ways in which Cold War cultural politics have shaped the legacy, reception, and discourse on the historic Bauhaus art school, focusing on American-German relations after 1945 and the role played by former Bauhäuslers, who had emigrated to the United States in the 1930s, in recording and then reinstating the historical narrative of this art school. A closer look at the narratives and omissions concerning the Bauhaus’ ideas, ideals, and practices will help to shed more light onto the question, why, up to this day, the focus remains on the Bauhaus under Walter Gropius between 1919 and 1928, neglecting the later Dessau years under Hannes Meyer and Mies van de Rohe.